Pengaruh E-Wom Dan Kepercayaan (Trust) Terhadap Keputusan Pembelian Dengan Minat Beli (Purchase Intention) Sebagai Variabel Intervening (Studi Kasus Pada Pengunjung Monokrom Store Yogyakarta) - Utami, Kesti Ayu; Welsa, Henny; Maharani, Bernadetta Diansepti (Universitas Muhammadiyah Metro, 2022)
The purpose of research into the influence of e-wom and trust affected the purchasing decision with interest in buying a variable intering in Monokrom Store Yogyakarta. The population in this study of Monokrom Store in yogyakarta, with a total of 120 respondents. Data collection methods use the questionnaire method distributed using the Accidental Purposive Sampling Technique. Research shows; (1) e-wom has a positive and significant impact on purchasing intentions, (2) trust has a positive and significant impact on purchasing intentions, (3) e-wom does not have a positive and significant impact on purchase decisions, (4) trust has a positive and significant impact on purchasing decisions, (5) the purchase intention has a positive and significant impact on purchasing decisions. In the test F acquired a value of 64.696 with significant 0,000 < 0.05 therefore e-wom and trust simultaneously affected the interest of the purchase. In the F test produced a value of 52.399 with the significance of 0,000 0.05 hence e-wom, trust and interest buying simultaneously affected the decision of the purchase.